Literacy Early Detection of Stunting Risk Factors in Women of Preconceptional Childbearing Age - Fitriani Umar; Rasidah Wahyuni Sari; Megawati; Melani Aspiranda; Warda J.; Sri Wulandari Rahman (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
The prevalence of stunting is mostly found in the first 1000 days of life (HPK), especially between birth and 2 years of age. The immediate causes of stunting are inadequate nutritional intake and recurring infectious diseases. Intervention for pregnant women and toddlers is a specific program in an effort to reduce the prevalence of stunting, but earlier prevention can be carried out if prospective pregnant women or women of preconceptional age are educated about the risks of stunting and its prevention. This community service activity aims to educate the public, especially women of childbearing age with preconceptions about stunting and early detection of risk factors. Activities are carried out in the form of education using booklets and flipcharts as media. Examination of the nutritional status of women of preconceptional childbearing age was carried out by measuring the upper arm circumference (Lila) and hemoglobin levels. Participants in the activity were women of preconceptional childbearing age and members of the Youth PKK, Watang Bacukiki Village, Parepare City. After providing education, the participants' knowledge about stunting and its risk factors increased. The results of measuring nutritional status found that 31.3% of participants experienced anemia and 18.8% experienced chronic energy deficiency (CED). It is hoped that from this activity, participants can carry out prevention and have independence in efforts to detect early risk factors for stunting.